AN ENHANCED CLUSTERING ALGORITHM IMPLEMENTED ON BIOLOGICAL DATA IN DATA MINING - DR.T.NALINI; S.REVATHI (International Journal of Pharma and Bio Sciences, 2013)
Bioinformatics is defined as the use of computer science and information theory to analyze biological systems. When people are injected vaccines, they may feel some side effects. Vaccine Adverse Event Reporting System (VAERS) is an awareness program launched in United States to monitor the people regarding their post vaccination period. VAERS is used to track the adverse events such as their disease, symptom, location of origin, age, gender, etc associated with these vaccines. KMeans clustering algorithm is used to cluster the similar data items which helps the active biologists of VAERS to gather relevant information about their patients. It’s very helpful to create awareness among the public regarding those vaccines. After each monitoring, the conditions of these patients are updated in the VAERS database. There are few queries listed below, that provides the similarity that exists between the patients of VAERS.